The Influence of Take and Give Learning Model on Students Learning Outcomes in Subhteme 2 The Importance of Clean Air for Health in Grade V UPTD SDN Pematang Siantar - Sulastri Menni Saragih; Natalina Purba; Esti Sirait (International Journal of Integrated Science and Technology, 2023)
This research aims to determine the influence of the Take and Give Learning Model on Student Learning Outcomes in Theme 2 Clean Air for Health, Subtheme 2 The Importance of Clean Air for Health in Class V UPTD Pematang Siantar Pilot Elementary School, the method in this research is a quantitative method in the form of an experiment. The research design is pre-experimental type one group pretest-posttest. The population and sample used were 26 students, with two research variables: the dependent variable (x) in the form of learning outcomes, and the independent variable (y) in the form of the Take and Give model. The data collection technique is the test technique. Test results using the t-test technique with the help of the spss program, based on the results of significant calculations (2-tailed) < 0.05, namely 0.000 < 0.05, tcount > ttable = 15.256 > 0.05, then Ho is rejected and Ha is accepted. So it can be concluded that there is an influence of the Take and Give learning model on student learning outcomes in subtheme 2 the importance of clean air for health in class V UPTD Pematang Siantar Pilot Elementary School.